(untitled) (Comprehensive Journal of Science, 2025)
Phenylketonuria (PKU) is a rare autosomal recessive metabolic disorder characterized by a deficiency in phenylalanine hydroxylase (PAH), leading to high concentrations of phenylalanine in the blood which can cause brain damage. This research focuses on evaluating the demographic patterns of PKU in the western region of Libya and assessing the effect of early intervention on neurodevelopmental outcomes. Data collection was done at El Galaa Hospital and subsequently analyzed using SPSS. Early diagnosis and dietary intervention to lower blood phenylalanine concentrations are crucial to help prevent the cognitive and behavioural complications that are associated with this disorder.